Pengaruh Latihan Single Leg Speed Hop Terhadap Peningkatan Daya Ledak Otot Tungkai Pemain Futsal Vamos Academy Padang - Raffiandy Alsyifa Putra; Apri Agus; Andri Gemaini; Didin Tohidin (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2022)
This research originated from the fact that there is still low limb muscle explosiveness of futsal players. Based on observations, the player's gastric kick is easily taken by the opponent when making a counterattack, often losing the jump of the player's heading time, and the player is always left behind in making the transition. Evidenced by preliminary studies to vamos academy padang futsal players randomly using standing broad jump test, obtained results with an average distance of 219.4 cm player jump, with the result can be known still low explosiveness of limb muscles vamos academy padang futsal players. The purpose of this study was to determine the effect of single leg speed hop exercises as free variables on the increase in limb muscle explosiveness as bound variables. This type of research is a pseudo experiment (quasi experiment) with the design of One Group Pre test-Post test. The population in this study was all Vamos Academy Padang futsal players who numbered 16 people. While the samples in this study amounted to 16 people taken with total sampling techniques. The research site is Glory Futsal Padang. The limb muscle explosiveness data in this study was taken using the Standing Broad Jump Test. The data analysis technique used for hypothesis testing in this study is to use the t-test formula with a significant level of 5%. It can be concluded that this study has a significant influence of single leg speed hop exercises on the increased limb muscle explosiveness of Vamos Academy Padang Futsal players